2009
DOI: 10.1103/physrevlett.102.164502
|View full text |Cite
|
Sign up to set email alerts
|

Micron-Scale Droplet Deposition on a Hydrophobic Surface Using a Retreating Syringe

Abstract: Droplet deposition onto a hydrophobic surface is studied experimentally and numerically. A wide range of droplet sizes can result from the same syringe, depending strongly on the needle retraction speed. Three regimes are identified according to the motion of the contact line. In Region I, at slow retraction speeds, the contact line expands and large droplets can be achieved. In Region II, at moderate needle speeds, a quasi-cylindrical liquid bridge forms resulting in drops approximately the size of the needle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 20 publications
4
37
1
Order By: Relevance
“…However, at an unstable state away from its critical state, the instability margin amplifies the critical perturbation, leading to more dramatic dynamics, which could impact the dispensed-drop size. As previously stated, Qian et al 24 reported small drop sizes in a pressure-controlled deposition due to fast dynamics near the contact line. Here, achieving a fast-receding contact line is assisted by the withdrawal of the liquid near primary and satellite drops upon stability loss at the maximum-height stability limit 19 .…”
Section: Contact-angle Hysteresis Effectsupporting
confidence: 52%
See 2 more Smart Citations
“…However, at an unstable state away from its critical state, the instability margin amplifies the critical perturbation, leading to more dramatic dynamics, which could impact the dispensed-drop size. As previously stated, Qian et al 24 reported small drop sizes in a pressure-controlled deposition due to fast dynamics near the contact line. Here, achieving a fast-receding contact line is assisted by the withdrawal of the liquid near primary and satellite drops upon stability loss at the maximum-height stability limit 19 .…”
Section: Contact-angle Hysteresis Effectsupporting
confidence: 52%
“…In the first two, U n ≪ u w , where u w is the capillary-wave speed; the contact line advances in the first and is stationary in the second with the drop size scaling as U −1/2 n ; the third corresponds to fast retraction speeds, U n /u w ∼ O(10 −2 ), where the dynamics dramatically change, and the drop size does not scale with U n as a simple power law. Here, the drop size is almost two orders of magnitude smaller than in the first two regimes, which Qian et al 24 attributed to a fast receding contact line with a speed approaching u w . However, in volume-controlled deposition, the dispensed-drop size did not exhibit the same sensitivity to the needle retraction speed in the parameter range studied by Qian and Breuer 25 .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Additives such as polymers and small particles can have a dramatic effect on the surface and rheological properties of small liquid droplets. These can, in turn, influence properties such as the wetting, spreading and dewetting behaviour of the fluids [3][4][5][6] . They also have a significant influence on their performance in applications such as droplet atomisation, ink jet printing, fuel injection 7 , microscale mixing/demixing 8,9 , and during drop impact and rebound phenomena 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Early investigations were motivated by applications such as liquid-jet breakup [2,3], crystal growth in microgravity [4], oil recovery [5], and paper wet strength [6]. Recently, interests have grown into areas such as elastocapillarity [7][8][9][10], contact-drop dispensing [11] with applications to scanning-probe lithography [12] and micromachined fountain-pen techniques [13]. Molecular-resolution surface patterning provides new opportunities for advanced tissue engineering [14], DNA self-assembled nanoconstructs [15], and highly sensitive protein chips [16].…”
Section: Introductionmentioning
confidence: 99%